2019
DOI: 10.3168/jds.2018-15269
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: Genetics, genome-wide association study, and genetic improvement of dairy fertility traits

Abstract: Before fertility traits were incorporated into selection, dairy cattle breeding primarily focused on production traits, which resulted in an unfavorable decline in the reproductive performance of dairy cattle. This reduced fertility is constantly challenging the dairy industry on the efficiency and sustainability of dairy production. Recent development of genomic selection on fertility traits has stabilized and even reversed the decreasing trend, showing the effectiveness of genomic selection. Meanwhile, genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 90 publications
4
75
0
1
Order By: Relevance
“…The sample for GWAS analysis contained 294,079 first lactation Holstein cows with phenotypic observations for five milk production traits (milk, fat and protein yields, and fat and protein percentages), three fertility traits (daughter pregnancy rate, cow conception rate, and heifer conception rate), and somatic cell score. Daughter pregnancy rate is the percentage of cows that become pregnant during each 21-d period, and cow and heifer conception rate each is defined as percentage pregnancy at each service (Ma et al, 2018). The number of phenotypic observations ranged from 294,079 for milk yield to 186,188 for cow conception rate (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample for GWAS analysis contained 294,079 first lactation Holstein cows with phenotypic observations for five milk production traits (milk, fat and protein yields, and fat and protein percentages), three fertility traits (daughter pregnancy rate, cow conception rate, and heifer conception rate), and somatic cell score. Daughter pregnancy rate is the percentage of cows that become pregnant during each 21-d period, and cow and heifer conception rate each is defined as percentage pregnancy at each service (Ma et al, 2018). The number of phenotypic observations ranged from 294,079 for milk yield to 186,188 for cow conception rate (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…GWAS in several dairy cattle breeds have reported a large number of QTL effects on dairy traits (Bolormaa et al, 2010; Pryce et al, 2010, 2014; Cole et al, 2011; Guo et al, 2012; Ma et al, 2012; Rothammer et al, 2013; Raven et al, 2014; Littlejohn et al, 2016; Jiang et al, 2017; Sanchez et al, 2017; Bouwman et al, 2018; Weller et al, 2018). However, the number of confirmed QTL effects across studies is low (Ma et al, 2018; Weller et al, 2018), and only limited understanding of the genetic mechanism of the QTL effects is available. The DGAT1 gene was widely confirmed to have the most significant effects for milk production (Grisart et al, 2002; Spelman et al, 2002; Schennink et al, 2007; Cole et al, 2011; Ma et al, 2012; Jiang et al, 2017), and previously was shown to have antagonistic pleiotropy effects between fat yield and milk and protein yields based on candidate causal variants (Thaller et al, 2003) or causal alleles (da Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have been successful at interrogating the genetic basis of complex traits and diseases in cattle [7][8][9][10]. Because complex traits are influenced by many genes, their interactions, and environment and due to the high level of linkage disequilibrium (LD) between genomic variants, pinpointing causal variants of complex traits has been challenging [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the proportion of the herd calving earlier in the year could be achieved through optimized reproductive management together with astute breeding decisions. Excellent reproductive performance is therefore key; considerable gains in performance have been achieved in most global dairy cow populations owing to genetic gain achieved following the consideration of reproductive performance in dairy cow breeding goals (Berry et al, 2014;Ma et al, 2019). In Ireland, for example, between the years 2010 and 2018, inclusive, there was an 8.2 percentage unit increase in the proportion of Irish dairy cows calving in January and February (ICBF, 2019).…”
Section: Management Factorsmentioning
confidence: 99%